RELEVANSI PENDIDIKAN KEJURUAN TERHADAP PASAR KERJA DI KOTA SALATIGA - Ngadi Ngadi (Research Centre for Population, Indonesian Institute of Sciences, 2014)
This paper aimed to discuss the relevance of vocational education on labor market mainly on labor absorption and productivity. Data for analysis are research data 2011 in Salatiga thatwerecollected by secondary data, interview, and observation. Analysis showed that vocational educations havehighcontribution onlabormarket. However, the relevance of vocational education to labor market has not been encouraging because about 12 percent of vocational education graduates are not absorbed in the labor market. In other sides, the average income of vocational educations graduates are lower than tertiary school graduates so the productivity of vocational education is still not satisfactory. Those were indicate that rate of return of vocational education lower than tertiary education. Thus, vocational educations need to be developed both in input and learning process so they can create more competitiveness graduation. Positively, some of the vocational educations have been able to make link and cooperation with business and industry.Even though, some of them have been able to get a good job before passed from school.education graduates are not absorbed in the labor market. In other sides, the average income of vocational educations graduates are lower than tertiary school graduates so the productivity of vocational education is still not satisfactory. Those were indicate that rate of return of vocational education lower than tertiary education. Thus, vocational educations need to be developed both in input and learning process so they can create more competitiveness graduation. Positively, some of the vocational educations have been able to make link and cooperation with business and industry.Eventhough, some of them have been able to get a good job before passed from school.This paper aimed to discuss the relevance ofvocational education on labor market mainly on laborabsorption and productivity. Data for analysis areresearch data 2011 in Salatiga thatwerecollected bysecondary data, interview, and observation. Analysisshowed that vocational educations havehighcontribution onlabormarket. However, the relevanceof vocational education to labor market has not beenencouraging because about 12 percent of vocationaleducation graduates are not absorbed in the labormarket. In other sides, the average income ofvocational educations graduates are lower thantertiary school graduates so the productivity ofvocational education is still not satisfactory. Thosewere indicatethat rate of return of vocationaleducation lower than tertiary education. Thus,vocational educations need to be developed both ininput and learning process so they can create morecompetitiveness graduation. Positively, some of thevocational educations have been able to make link andcooperation with business and industry.Eventhough,some of them have been able to get a good job beforepassed from school.This paper aimed to discuss the relevance of vocational education on labor market mainly on labor absorption and productivity. Data for analysis are research data 2011 in Salatiga thatwerecollected by secondary data, interview, and observation. Analysis showed that vocational educations havehighcontribution onlabormarket. However, the relevance of vocational education to labor market has not been encouraging because about 12 percent of vocationaleducation graduates are not absorbed in the labor market. In other sides, the average income of vocational educations graduates are lower than tertiary school graduates so the productivity of vocational education is still not satisfactory. Those were indicate that rate of return of vocational education lower than tertiary education. Thus, vocational educations need to be developed both in input and learning process so they can create more competitiveness graduation. Positively, some of the vocational educations have been able to make link and cooperation with business and industry.Eventhough, some of them have been able to get a good job before passed from school.This paper aimed to discuss the relevance ofvocational education on labor market mainly on laborabsorption and productivity. Data for analysis areresearch data 2011 in Salatiga thatwerecollected bysecondary data, interview, and observation. Analysisshowed that vocational educations havehighcontribution onlabormarket. However, the relevanceof vocational education to labor market has not beenencouraging because about 12 percent of vocationaleducation graduates are not absorbed in the labormarket. In other sides, the average income ofvocational educations graduates are lower thantertiary school graduates so the productivity ofvocational education is still not satisfactory. Thosewere indicatethat rate of return of vocationaleducation lower than tertiary education. Thus,vocational educations need to be developed both ininput and learning process so they can create morecompetitiveness graduation. Positively, some of thevocational educations have been able to make link andcooperation with business and industry.Eventhough,some of them have been able to get a good job beforepassed from school.